Serological reactivity of different antigenic preparations of Leishmania (Leishmania) amazonensis and the Leishmania braziliensis complex - Gomes-Silva,Adriano (2008)
Total antigen from Leishmania (Leishmania) amazonensis and isolates from the Leishmania braziliensis complex, along with their respective antigenic fractions obtained by affinity chromatography on concanavalin-A-Sepharose and jacalin-agarose columns evaluated using immunoenzymatic ELISA assay. For this, serum samples from 229 patients were used, grouped as American tegmental leishmaniasis (nº=58), visceral leishmaniasis (nº=28), Chagas disease (nº=49), malaria (nº=32), tuberculosis (nº=13) and healthy volunteers (nº=49). Samples from American tegmentary leishmaniasis showed higher reactivity with antigens isolated from the Leishmania braziliensis complex than with antigens from Leishmania amazonensis (p<0.001). ELISA assays showed a sensitivity range from 60% to 95% with antigens isolated from the Leishmania braziliensis complex. There was marked nonspecific reactivity among serum samples with the use of antigenic fractions binding with concanavalin-A and jacalin from both Leishmania complexes, in comparison with other antigens (p<0.001). The results presented in this study suggest that the use of homologous antigens increases the efficiency of anti-Leishmania immunoglobulin detection, which may be very valuable for diagnostic purposes.